Implementasi Strategi Guru Bimbingan Dan Konseling Dalam Mengatasi Perilaku Perundungan Pada Remaja Awal (12-15 tahun) - Tohari, Sabit; Prasetia, Muhammad Eka (JURNAL KONSELING GUSJIGANG, 2023)
This study aims to determine the Implementation of Guidance and Counseling Teacher Strategies in Overcoming Bullying Behavior in Early Adolescents (12-15 years). The approach in this study uses a qualitative approach with a phenomenological research design. The method used in this study in collecting data is to use interview and documentation techniques, which will then be analyzed and seen for the validity of the data using data triangulation techniques. The output target of this research is as intellectual material on strategies to overcome bullying behavior, as consideration for guidance and counseling teachers. The results obtained are based on data from interviews with 2 BK teachers and 4 students as well as data from documentation. From these results it was found that the implementation of the BK teacher's strategy in overcoming bullying behavior was going well, this was proven to have greatly reduced the bullying behavior that occurred at SMPN 17 Banjarmasin. although there are obstacles in implementing these strategies, these obstacles come from the parents of students, from the students themselves, and lack of time. to provide individual counseling services and information service.